Clinical Spectrum and Etiology of Pediatric Fulminant Hepatic Failure in Pakistan - Rabia Ahmad, Aftab Anwar, Sommayya Aftab, Huma Arshad Cheema (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the clinical spectrum and etiology of pediatric fulminant hepatic failure (FHF) in Pakistan. Study Design: Prospective, cross sectional study Place and Duration of Study: Department of Pediatric Gastroenterology, Hepatology & Nutrition, the University of Child Health & the Children’s Hospital, Lahore, from December 2013 to March 2016. Materials and Methods: Patients 2 -15 years, admitted in the unit with FHF, were included after taking informed consent from the parents, employing consecutive sampling. FHF was defined as presence of acute liver failure (INR>2.0) with/without hepatic encephalopathy, without preexisting liver disease, within 8 weeks of the onset of clinical liver disease. Patients with preexisting liver disease, systemic disease such as hemophagocytic lymphohistiocytosis or leukemia were excluded. Results: Total 85 patients, who fulfilled the inclusion and exclusion criteria, were admitted during the study period. There was a slight male predominance (54.1%) with mean age as 6.3±3.8 years. The largest age group (54.1%) comprised of younger children with age 2-5 years. Infectious causes were most common (52.9%) in our participants followed by undetermined etiology (15.3%). More than 50% of patients has good outcome. Conclusion: Hepatitis A was the most common etiological agent of pediatric FHF. Majority of children improve with supportive care.